IMPLEMENTASI WEB SCRAPING UNTUK PENGUMPULAN DATA MEDIA SOSIAL LINGKUP PEMERINTAH PROVINSI NTB - Hidayati, Lilik; Kusuma, Logananta Puja; Agustini, Dwi; Ardhana, Valian Yoga Pudya (Jurnal Sistem Informasi dan Informatika (Simika), 2024)
The number of internet users in Indonesia has recently increased, currently reaching around 62.1% of the total population. The prevalence of social media use has provided benefits for many stakeholders to be involved in the socialization and promotion of their products and activities. Information regarding the latest government programs and activities is published through the official website of the West Nusa Tenggara Provincial Government and the official pages of each office within the West Nusa Tenggara Provincial Government. The potential of social media needs to be maximized in order to disseminate government programs and activities to the community. Social media offers governments the potential to increase democratic participation by encouraging the public to have a voice in policymaking, working with the public to improve services, gathering ideas, and increasing transparency. This research seeks to apply web scraping techniques to collect data with the aim of monitoring social media performance and identifying factors that are closely related to the level of response elicited by a social media post. The research results show that on average a post on the official page of the West Nusa Tenggara Provincial Government gets around 114.9 likes, 5.1 comments and 11.6 shares. Importantly, one of the important factors that influences the number of likes a post receives is the time it is published. Optimal publication times for the official pages of the West Nusa Tenggara Provincial Government are observed between 06.00-16.00 and 18.00-21.00. By looking closely at social media performance and identifying these influencing factors, social media managers are ready to gain invaluable insights to improve performance by precision and efficacy.